Genetic control of Salmonella typhimurium-induced depression of delayed-type hypersensitivity to sheep erythrocytes in mice. - Nauciel, C (1988)
Infection of mice with a temperature-sensitive mutant of Salmonella typhimurium C5TS allowed the survival of genetically susceptible mice. The ability to mount a delayed-type hypersensitivity (DTH) response to sheep erythrocytes during infection with C5TS was studied in various inbred mouse strains, recombinant inbred strains derived from C57BL/6 (susceptible) and A/J (resistant) mice, and C3H congenic mice. Suppression of the DTH response to sheep erythrocytes was found in mice that carried the Itys allele, the H-2b haplotype, or both. These genes are known to increase susceptibility to S. typhimurium infection. In contrast, no DTH response suppression was observed in mouse strains that carried other genes that increased susceptibility to S. typhimurium, e.g., DBA/2 and C3H/HeJ. Apart from a transient suppression in A/J mice, the DTH responses of resistant mice (A/J and CBA) were normal or increased. The DTH response to sheep erythrocytes could be restored in immunodepressed mice by increasing the immunizing dose, suggesting the possible role of activated macrophages in depression of the DTH response.